Interaction of functional gastrointestinal disorders with postpartum conditions related to mother and baby - Bekem, Özlem; Günay, İlker; Çelik, Filiz; Apa, Hurşit (The Turkish Journal of Pediatrics, 2021)
Background. Functional gastrointestinal disorders (FGID) may affect or may be affected by postpartum depression (PPD), mode of feeding and postpartum life quality. We aimed to evaluate the interaction between FGID and these parameters in infants. Methods. The study group consisted of babies attending our outpatient clinics. There were three age groups: 4-6 weeks, 3-4 months and 6-7 months. Demographic data of the babies and mothers, and data of feeding were collected. For the diagnosis of FGID, Rome III criteria were used. Mothers were screened with the Edinburgh Depression Scale. Quality of life (QoL) scores were obtained by using the `Maternal Postpartum Quality of Life Questionnaire`. Factors affecting the presence of FGID, PPD and quality of life were analyzed. Results. Two hundred thirteen infants were enrolled during the study period. FGID was present with similar rates in both genders and was lower (31.5%) in the 6-7 month-old group (p=0.001). Infantile colic was higher in girls (68.6% vs. 31.4%, p=0.016). In 4-6 week-old infants with infantile dyschesia, the delivery route was mostly cesarean (83.3% vs. 16.7%, p=0.006). Similarly, regurgitation was more frequent in 6-7 month-old infants born by cesarean (88.9% vs. 11.1%, p=0.035), and was more frequent in infants being exclusively breastfed (60.9%, p=0.037). QoL scores were lower in mothers with depression (20.9±3.4 vs. 23.9±3.6, p=0.003). Infantile colic was higher in mothers with depression, but not significantly (29.3% vs. 11.4%, p=0.057). Conclusions. Caesarian section delivery and breastfeeding were influential on infantile dyschesia and regurgitation subgroups. No other studied factor seemed to affect FGID.
Keywords: breastfeeding; functional gastrointestinal disorders; infants; life quality; postpartum depression